(untitled) (LACCEI, 2024)
Social Innovation Laboratories are spaces that promote co-creation to solve social problems, through the application of innovation processes and technology for social appropriation. They link the university with the community, the strategies of university practices, extension and social projection, and civil society. Technological innovations drive quality education systems and foster meaningful learning. Through remote laboratories, it is possible to have access to laboratory instruments or machines to carry out practices or experiments in real time, regardless of time or geographic location. One strategy to reduce poverty and inequality is to ensure that vulnerable communities have access to energy services. Most of the energy production is from fossil fuels, which generates greenhouse gases that represent a health risk. It is imperative to deepen measures focused on energy saving, greater energy efficiency and the progressive incorporation of energy sources with low environmental impact. This is how innovation laboratories arise within the framework of energy sustainability. This paper presents the results of applying different energy systems from renewable sources through the simulation of energy changes in remote laboratories with the aim of strengthening the skills that allow students to generate strategies and specific actions to promote sustainable development in marginalized communities, transform them into off-grid communities and improve their quality of life. The results show the development of disciplinary and transversal competences with the proposed methodology, because digital tools allow activities to be carried out with sufficient fidelity to achieve meaningful learning and training in energy sustainability.